Memahami Strategi Financial Management Bagi Siswa SMK Bina Patriot - Ririn Uke Saraswati; Sri Winda Hardiyanti Damanik; Soedjatmoko Soedjatmoko; Arrofie Darmawan; Sony Sonjaya; Fenika Bunga Prawida Suwanto; Khairil Anwar; Sandi Arif Setiadi; Winda Neri Sari (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Financial management is a field of management related to planning, examining, controlling, managing and storing activities carried out by individuals, organizations or companies. The importance of understanding financial management strategies well is not only for workers who already have income, but also for students who will one day enter the workforce and will have their own income. Community service activities with the theme